Hubungan Pengetahuan Orang Tua tentang Pneumonia dan Pneumococcal Conjugate Vaccine dengan Penerimaan PCV di Sleman - Ghofur Hariyono; Sri Hartini; Ayyu Sandhi (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2026)
Background: Pneumonia remains a cause of mortality among Indonesian infants and children under five. Since 2022, Pneumococcal Conjugate Vaccine (PCV) has been included in the national immunization program. Parental knowledge and acceptance influence PCV immunization among children. Studies in Indonesia regarding knowledge of pneumonia, PCV immunization, and PCV acceptance remain limited. Objective: To analyze the relationship between parental knowledge of pneumonia and PCV immunization and PCV acceptance. Methods: A cross-sectional study was conducted at 28 posyandu in Sleman involving 288 parents of children aged 0–2 years, excluding children with contraindications to PCV immunization. Proportionate stratified random sampling was used to determine sample size in each village, while posyandu were randomly selected in March 2025. Data were collected using validated questionnaires consisting of 13 knowledge and 9 acceptance items (r > 0,244), with KR-20 = 0,723 and Cronbach’s alpha = 0,707. Spearman’s Rho and Mann–Whitney tests analyzed relationships between characteristics, knowledge, and acceptance. Multiple linear regression identified the main predictor of acceptance. Results: A total of 73,6% of parents had good knowledge. Positive acceptance included pneumonia burden (89,2%), PCV benefits (91,7%), PCV financing (95,1%), willingness to immunize children (96,5%), and PCV socialization (93,4%). Knowledge was associated with PCV acceptance (r = 0,173; p = 0,003) and was the dominant factor (β = 0,296). Education (p = 0,023), health insurance ownership (p = 0,034), and experience (p = 0,001) were also associated with PCV acceptance. Conclusion: Better parental knowledge of pneumonia and PCV immunization was associated with positive PCV acceptance.INTISARILatar belakang: Pneumonia masih menjadi salah satu penyebab kematian bayi dan balita di Indonesia. Sejak tahun 2022, Pneumococcal Conjugate Vaccine (PCV) telah menjadi program imunisasi nasional. Pengetahuan dan penerimaan orang tua memengaruhi pemberian imunisasi PCV pada anak. Penelitian di Indonesia terkait pengetahuan pneumonia dan imunisasi PCV serta penerimaan PCV masih terbatas. Tujuan: Menganalisis hubungan pengetahuan orang tua tentang pneumonia dan imunisasi PCV dengan penerimaan PCV. Metode: Penelitian cross-sectional di 28 Posyandu di Sleman melibatkan 288 orang tua anak usia 0–2 tahun, dengan kriteria eksklusi anak yang memiliki kontraindikasi imunisasi PCV. Proportionate stratified random sampling digunakan untuk menentukan sampel tiap kalurahan, sedangkan Posyandu dipilih secara acak pada Maret 2025. Data dikumpulkan menggunakan kuesioner tervalidasi yang terdiri dari 13 item pengetahuan dan 9 item penerimaan (r > 0,244), dengan KR-20 = 0,723 (pengetahuan) dan Cronbach’s alpha = 0,707 (penerimaan). Uji Spearman’s Rho dan Mann–Whitney digunakan untuk menganalisis hubungan karakteristik, pengetahuan, dan penerimaan. Regresi linier berganda mengidentifikasi prediktor utama penerimaan. Hasil: Sebanyak 73,6% orang tua memiliki pengetahuan baik. Penerimaan positif mencakup persepsi beban pneumonia (89,2%), manfaat PCV (91,7%), pembiayaan PCV (95,1%), kesediaan imunisasi (96,5%), dan sosialisasi PCV (93,4%). Pengetahuan berhubungan dengan penerimaan PCV (r = 0,173; p = 0,003) dan menjadi faktor paling dominan (β = 0,296). Pendidikan (p = 0,023), kepemilikan asuransi kesehatan (p = 0,034), dan pengalaman (p = 0,001) juga berhubungan dengan penerimaan PCV. Simpulan: Semakin baik pengetahuan orang tua dari anak usia 0–2 tahun tentang pneumonia dan imunisasi PCV, semakin positif penerimaan terhadap imunisasi PCV.